The Influence of Credit Procedures, Service Quality and Bank Location on the Decision to Take People's Business Credit (KUR) - Sutjipto, Mohammad Riza; Awaluddin, Muhammad; Nastassya, Nastassya (Journal of Comprehensive Science, 2025)
People's Business Credit (KUR) is a government financing program designed to encourage the growth of the MSME sector. This study aims to analyze the influence of credit procedures, service quality, and bank location on the decision to take KUR at PT. Bank Mandiri (Persero) Tbk KCP Dumai Syarif Kasim. The research method used a quantitative approach with multiple linear regression analysis of 100 respondents selected by purposive sampling. The results of the study showed that, simultaneously, the three variables had a significant effect on the decision to take KUR (F-count = 372.424, p < 0.05). Partially, only credit procedures had a positive and significant effect (? = 0.467, t = 15.06, p < 0.05). The quality of service did not show a significant effect (? = -0.007, t = -0.24, p > 0.05), while the location of the bank had a significant negative effect (? = -0.532, t = -22.17, p < 0.05). The adjusted R² value of 0.921 indicates that 92.1% of the variation in the decision to take KUR is explained by all three variables. These findings confirm that procedural efficiency is a major factor in KUR decision-making, while perceptions of bank services and physical locations are not always the main considerations in the digital age.